Avocado Seed Ethanol Extract's Ability to Reduce Hyperuricemia in Mice - Sylvia Winata; Rena Meutia; Astriani Natalia; Asyrun Alkhairi Lubis (Yayasan Penelitian dan Inovasi Sumatera, 2025)
Background: Hyperuricemia causes uric acid buildup in the blood, often in older people due to how the body processes purines. Studies show avocado seeds (Persea americana Mill.) may reduce blood uric acid through their flavonoid content, which fights off oxygen molecules and reduces inflammation, stopping a process called xanthine oxidation. Objective: This study aims to assess the effectiveness of avocado seed extract in lowering uric acid levels in male mice. Method: Mice were induced with potassium bromate, and the mice were divided into six groups of five individuals each. The groups included a negative control (Na CMC 0.5%), a positive control (allopurinol 10 mg/kg BW), treatment 1 (avocado seed extract 120 mg/kg BW), treatment 2 (avocado seed extract 150 mg/kg BW), treatment 3 (avocado seed extract 180 mg/kg BW), and a normal group (not treated). Checked uric acid levels for seven days. Then, used a statistical test and a BNT test with the LSD method to examine the results. Results: The findings showed that avocado seed extract given at a dose of 120-180 mg/kg body weight can reduce uric acid levels in mice. Conclusion: The best dose, 150 mg/kg BW, reduced hyperuricemia levels by 37.3%, with a significance value of 0.118